Rearranging x+y-xr solve for y

QUESTION POSTED AT 29/05/2020 - 01:07 AM

Answered by admin AT 29/05/2020 - 01:07 AM

The value of y = x(r -1)

Given expression is : x+y-xr 

Now, on rearranging the terms of the expression we get,

x -xr + y
Now, we put it equal to zero to find the value:

x -xr + y = 0
⇒ y = xr -x (The signs changes on moving from left-hand side of the equation to the right hand side)
⇒ y = x(r -1)

Post your answer

Related questions

How would i solve something like 15/3?

QUESTION POSTED AT 01/06/2020 - 04:47 PM

Solve for x. x = ln 1 x =

QUESTION POSTED AT 01/06/2020 - 03:37 PM

Solve the formula d=st for s

QUESTION POSTED AT 01/06/2020 - 03:24 PM

Solve for x 3/2x+5=1/9x A.1/5 B.1/2 C.5/3 D.16/5

QUESTION POSTED AT 01/06/2020 - 02:29 PM